The Attitude And Intentions Of Millennials Towards Digital Banks In The Post-Pandemic Era - Stefanus Cahya Catur Wijaya; Luh Putu Mahyuni (Green Publisher Indonesia, 2024)
Pandemic Covid-19 has had a significant impact on Indonesia’ economic since March 2020 and affecting every single aspect of life including financial and banking system. Banking create innovation through technology, and it’s called Digital Bank. Now Pandemic has end, but millennials attituded, and intention banking are change? This research held to understand the attitude and intention of millennials toward Digital Banks in the post pandemic era using quantitative method and using TAM to understand the intention with e-trust and attitude toward using digital bank as mediation. The result from this research show that Perceived usefulness, perceived ease of use, and e-trust strongly influence millennial’s intention to adopt digital bank. E-trust have significate mediation between perceived ease of use and behavior intention. Conclusion is designing marketing strategies or technology development requires consideration of perceived usefulness, ease of use, and e-trust, alongside factors like social influence and attitude toward usage. Understanding these relationships enables organizations to more effectively influence individuals' intentions to adopt new technology. Furthermore, recommendations for further research include conducting comparative studies across various technologies, exploring the influence of culture, employing multidisciplinary approaches, and conducting in-depth qualitative research to gain deeper insights into user behavior related to technology adoption.